STRATEGI GURU DALAM MENGATASI HAMBATAN ARTIKULASI PADA SISWA TUNADAKSA DI KELAS INKLUSIF - Hayu Azhari R; Ananda Syahputri Harahap; Siti Nur Isnaini Ramadanisa; Oktavia Nabila; Ramadhani (LPPI UMN AL WASHLIYAH, 2026)
Articulation barriers in students with physical disabilities in inclusive classrooms represent a significant challenge affecting communication and learning processes. This study aims to identify and describe strategies used by teachers in overcoming articulation barriers in physically disabled students in inclusive classes, particularly regarding communication methods, pause provision (wait time), and instructional techniques that minimize psychological pressure when students speak. The research was conducted using a descriptive qualitative approach through in-depth observation, interviews, and questionnaires administered to teachers, physically disabled students, and parents at four inclusive elementary schools in Medan City. The results indicate that the most effective teacher strategies include the use of multimodal communication, provision of adequate wait time, application of step-by-step instruction, and the creation of a safe and pressure-free classroom environment. It is concluded that inclusive communication strategies significantly increase the confidence of physically disabled students in speaking and actively participating in class. Keywords: articulation, physical disability, inclusive classroom